RECONSTRUCTING ABSENTEE LAND POLICY: A PROPORTIONALITY ANALYSIS OF PROPERTY RIGHTS PROTECTION WITHIN THE FRAMEWORK OF AGRARIAN JUSTICE - Fernando Tantaru (Faculty of Law Sriwijaya University, 2026)
This study examines the regulation of absentee land ownership in Indonesia from the perspective of property rights protection using the proportionality principle. While the prohibition of absentee land is intended to promote agrarian justice, its continued application raises questions regarding its relevance in contemporary socio-economic conditions. Increased mobility, diversified land management practices, and evolving land-use patterns challenge the assumption that land must be directly cultivated by its owner. This research employs a normative legal method with a conceptual and statutory approach, analyzing absentee land regulation through the stages of legitimate aim, necessity, and proportionality stricto sensu. The findings indicate that although the policy satisfies the requirement of legitimate aim, it encounters significant limitations in meeting the criteria of necessity and proportionality. The absence of clear legal standards, particularly in defining unmaintained land, creates legal uncertainty and expands administrative discretion, potentially leading to disproportionate restrictions on property rights. This study proposes a reconstruction of absentee land policy through a shift toward a productivity-based regulatory framework, supported by measurable indicators and strengthened procedural safeguards. The study contributes to the development of agrarian law by integrating proportionality analysis into the evaluation of land regulation and offering a more balanced approach between agrarian justice and constitutional property rights protection.